TERIPANG SEBAGAI SALAH SATU SUMBER KOLAGEN - Bayu Kumayanjati (OSEANA, 2020)
Sea cucumbers are one of the Echinoderms that are rich in nutrients. Sea cucumbers contain a lot of minerals, unsaturated fatty acids, amino acids, and quite high protein. Protein content in sea cucumbers can reach 40% depending on the type and habitat of the sea cucumber. High protein content in sea cucumbers has the potential as a source of collagen. Collagen is a constituent protein found in the skin, tendons, cartilage and hard bones, and other tissues. Collagen currently has been widely applied in various industrial fields, such as cosmetics, health, pharmacy and food, so that the requirement for collagen will increase. Collagen currently is still dominated by collagen from cattle and pigs. Collagen from cattle is the most widely used in Indonesia because the halal collagen is important in Indonesia. The requirement for halal collagen will certainly be limited if it only relies on collagen from cattle. Therefore, alternative sources of collagen are needed, one of them is sea cucumbers.